The art information professional in the Philippines continuing professional development needs of librarians in art and design libraries - Madlangsakay, Efren S. Jr (2009)
The study conducted aimed to find out what areas in the field of art and design information professionals see as most important in relation to their pursuance of continuing professional education as well as the factors that affect them in taking continuing education programs.